Gastric Duplication in a Preterm Neonate - Atraya Samanta; Saugata Acharyya; Kakoli Acharyya; Biswajit Bhaduri (Wolters Kluwer Medknow Publications, 2022)
Background: Gastrointestinal (GI) duplication is defined as a spherical structure with a muscular coat and is lined by a mucous membrane. It is a rare congenital anomaly. Clinical Description: A preterm baby born, delivered at 31 weeks, was diagnosed with respiratory distress syndrome and managed as per hospital protocol. While being weaned off from nasal continuous positive airway pressure, feeding was started. He developed vomiting and epigastric distension within 6 h. Management: The baby was investigated for the cause, and an early-onset sepsis was excluded. X-ray abdomen showed distended stomach and gas shadows in the bowel loops. Ultrasound did not reveal any gastric outlet obstruction, but significant gaseous distension of the stomach prompted us to make a dye study of the upper GI tract, which revealed cystic outpouching of the stomach that communicated with the gastric lumen. Similar findings were seen on computed tomographic scanning. Exploratory laparotomy performed revealed a large cyst communicating with the stomach at the lesser curvature. This was dissected out entirely from the margin of the stomach. Histopathology revealed highly congested cyst wall with an inner lining of gastric epithelium and gastric glands and an outer smooth muscle coat, confirming a gastric duplication cyst. Conclusion: Gastric duplication should be considered as a differential in newborns with feed intolerance, epigastric distension, and significant distension of the stomach. Although serial radiological investigations provide supportive evidence for this condition, the diagnostic confirmation is obtained by gross inspection and histopathology. In view of high risk of malignant transformation, surgical resection of the entire cyst remains the most definitive management.